A framework for 3D synthetic mesoscale models of hot mix asphalt for the finite element method. (1st September 2017) - Neumann, J.; Simon, J.-W.; Mollenhauer, K.; Reese, S.
Highlights: An algorithm to create 3D synthetic mesoscale models of hot mix asphalt is presented. Particle size distributions are captured by nested Voronoi tessellations. The complex shear modulus and loss angle are predicted using the finite element method. The representative volume element size is found to increase reciprocally to loading frequency. Abstract: A versatile framework to create 3D mesoscale models of hot mix asphalt is presented. The mortar phase of a German standard hot mix asphalt is tested in the linear viscoelastic regime using a modified dynamic shear rheometry setup. The widely used generalised Maxwell-model is fit to master-curve data. Virtually any particle size distribution can be matched by a nested Voronoi tessellation algorithm, which is shown by generating geometrical models for three different types of hot mix asphalt. Several techniques to reduce the computational effort are introduced at the geometry and mesh levels. Representative volume elements for mixture SMA 8 S are determined and used to predict the complex shear modulus and loss angle. An analysis of the reinforcing properties of the mineral aggregate phase is presented. The influence of the loading rate on the size of representative volume elements is investigated.